Apoptotic pathways as targets for novel therapies in cancer and other diseases - Los, Marek. (Springer US, 2025)
As our understanding of apoptotic pathway expands, we are coming to realize the great potential of utilizing this pathway to treat diseases such as cancer. The book attempts to review, summarize, and speculate on the apoptotic pathways, how are they regulated and how targeted therapies are being used to treat a wide variety of diseases. Special emphasis is placed on cancer since new treatments either being developed or currently in the clinical setting are showing great promise to increase survival rates for cancer patients. Chapters will address the biology behind regulating the apoptotic pathways and what goes wrong in disease states whereas other chapters will concentrate on new therapies targeting apoptotic pathways. The reader by the end of the book should have greater insight into the understanding and utilization of apoptotic pathways to fight diseases such as cancer. Apoptotic pathways and their regulation -- Mechanisms of anticancer drug action -- Death receptor pathways as targets for anticancer therapy -- Caspases ; modulators of apoptosis and cytokine maturation — targets for novel therapies -- The intrinsic (mitochondrial) death pathway and new cancer therapeutics: BCL-2 family in focus -- survivin, other IAPS, SMAC/DIABLO, and OMI/HTRA2 — modulation of the advancing apoptotic process -- The life cycle of p53: a key target in drug development -- Growth factors, receptors, and kinases : their exploration to target cancer -- Targets for apoptotic intervention in rheumatoid arthritis -- Therapeutic inhibition of apoptosis caused by stroke -- Monoclonal and bispecific antibodies as novel therapeutics -- targeting the proteasome in cancer therapy -- D-RNAi-based therapeutics -- Nuclear transcription factor-kB: a drug target for all seasons -- Monitoring of programmed cell death in vivo and in vitro,—new and old methods of cancer therapy assessment -- Current strategies in tumor-targeting -- Strategies of protection of normal cells during chemo- and radio-therapy based on modulation of cell cycle and apoptotic pathways.